Effects of excitation angle strategy on quantitative analysis of hyperpolarized pyruvate. Issue 6 (22nd February 2019) - Walker, Christopher M.; Fuentes, David; Larson, Peder E.Z.; Kundra, Vikas; Vigneron, Daniel B.; Bankson, James A.
Abstract : Purpose: Various excitation strategies have been proposed for dynamic imaging of hyperpolarized agents such as [1‐ 13 C]‐pyruvate, but the impact of these strategies on quantitative evaluation of signal evolution remains unclear. To better understand their relative performance, we compared the accuracy and repeatability of measurements made using variable excitation angle strategies and conventional constant excitation angle strategies. Methods: Signal evolution for constant and variable excitation angle schedules was simulated using a pharmacokinetic model of hyperpolarized pyruvate with 2 chemical pools and 2 physical compartments. Noisy synthetic data were then fit using the same pharmacokinetic model with the apparent chemical exchange term as an unknown, and fit results were compared with simulation parameters to determine accuracy and reproducibility. Results: Constant excitations and a variable excitation strategy that maximizes the HP lactate signal yielded data that supported quantitative analyses with similar accuracy and repeatability. Variable excitation angle strategies that were designed to produce a constant signal level resulted in lower signal and worse quantitative accuracy and repeatability, particularly for longer acquisition times. Conclusions: These results suggest that either constant excitation angle or variable excitation angles that attempt to maximize total signal, as opposed to maintaining a constant signal level, are preferred for metabolic quantification using hyperpolarized pyruvate.